write factors of a^3 - b^3
Answers
Answered by
4
Hi,
Here is your answer
a³ - b³ = (a - b)³ + 3ab (a - b)
= (a - b)³ + 3a²b - 3ab²
= (a - b)³ + 3ab (a - b)
= (a - b) [(a - b)² + 3ab)
= (a - b) (a² + b² - 2ab + 3ab)
= (a - b) (a² + b² + ab)
Therefore the factors of a³ - b³ are (a - b) (a² + b² + ab).
Hope this helps you.
Here is your answer
a³ - b³ = (a - b)³ + 3ab (a - b)
= (a - b)³ + 3a²b - 3ab²
= (a - b)³ + 3ab (a - b)
= (a - b) [(a - b)² + 3ab)
= (a - b) (a² + b² - 2ab + 3ab)
= (a - b) (a² + b² + ab)
Therefore the factors of a³ - b³ are (a - b) (a² + b² + ab).
Hope this helps you.
Similar questions